2018
DOI: 10.1111/iju.13524
|View full text |Cite|
|
Sign up to set email alerts
|

Laparoscopic adrenalectomy using the lateral retroperitoneal approach: Is it a safe and feasible treatment option for pheochromocytomas larger than 6 cm?

Abstract: Objectives: To evaluate the surgical feasibility of laparoscopic adrenalectomy using the lateral retroperitoneal approach for the treatment of large pheochromocytomas, and to identify the preoperative risk factors for intraoperative hypertension. Methods: We retrospectively reviewed 51 patients who underwent laparoscopic adrenalectomy using the lateral retroperitoneal approach for the treatment of pheochromocytomas. Patient characteristics and perioperative outcomes were analyzed and compared between the two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 31 publications
4
30
3
Order By: Relevance
“…However, it was also mentioned that retroperitoneal approach requires a significant learning curve and that it’s a difficult procedure in obese patients 11. Chung et al reported the feasibility of laparoscopic adrenalectomy using retroperitoneal approach for large size PCC and outcomes were comparable 12. Both the techniques are similar and outcomes are comparable in the hands of experienced laparoscopic experts in field of urology.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also mentioned that retroperitoneal approach requires a significant learning curve and that it’s a difficult procedure in obese patients 11. Chung et al reported the feasibility of laparoscopic adrenalectomy using retroperitoneal approach for large size PCC and outcomes were comparable 12. Both the techniques are similar and outcomes are comparable in the hands of experienced laparoscopic experts in field of urology.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding large pheochromocytoma, Chung et al . reported that RPA was a safe and feasible approach, but there was no comparison with TPA …”
Section: Discussionmentioning
confidence: 99%
“…18 Regarding large pheochromocytoma, Chung et al reported that RPA was a safe and feasible approach, but there was no comparison with TPA. 12 An investigation into which approach is preferable for large pheochromocytoma has been warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations